Fabrication and characterization of carbon nanotube field emitters - Jiao, J; Dong, L; Tuggle, D; Mosher, C; Foxley, S; Tawdekar, J (2002)
We report an effective procedure for fabricating carbon nanotube emitters by directly synthesizing carbon nanotubes on an electrochemically sharpened tungsten tip. The nanotubes adhere very well to the tip of tungsten without any painting materials. Thermal cleaning of the tungsten tip under applied electric field reduced the number of nanotubes formed on the tip resulting in a single nanotube emitter. Electron field emission properties were investigated by employing a field emission microscope with a base pressure ∼ 1 × 10-9 Torr. The emission images with respect to the applied field and time were obtained. Different emission images consisting of one to four lobes at different applied fields were observed. The characteristic of the emission current vs. applied voltage was analyzed. Applied potentials up to 3000 V were tested. The estimated field on the emitter was on the order of several tens of volts per nanometer. Our investigation suggests that at lower fields, the I-V characteristic of the nanotube emitter follows Fowler-Nordheim (F-N) emission behavior. At higher applied field, current saturation was observed.